2022
DOI: 10.24952/ee.v10i2.6749
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception toward Good Lecturer Pedagogical Competence

Abstract: As the application of the four competencies for the lecturers in teaching and learning becomes a new business for them to fulfil those competencies (pedagogical, professional, personality, social). This impacts the provision of a new method for students in learning activities so that a teacher could develop a curriculum per the respective educational unit and the local needs of each student. The first pedagogical competence deals with a lecturer's ability to manage the classroom and facilitates the students’ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Teachers and students may have different perspectives on lecturers' pedagogical competence. A case study by Rahman (2022) found that lecturers' perspective of their pedagogical competence includes mastering material, preparing learning objectives, accommodating the students' needs and controlling the classroom situation. While students have different perspectives that a competent teacher should be ready to deliver the material, able to enliven class conditions, able to give feedback and evaluation on students' tasks, and last but not least, able to use media and technology in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers and students may have different perspectives on lecturers' pedagogical competence. A case study by Rahman (2022) found that lecturers' perspective of their pedagogical competence includes mastering material, preparing learning objectives, accommodating the students' needs and controlling the classroom situation. While students have different perspectives that a competent teacher should be ready to deliver the material, able to enliven class conditions, able to give feedback and evaluation on students' tasks, and last but not least, able to use media and technology in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…However, understanding competencies tends to be unspecified and general [6]. Teachers' pedagogical competence is culture-specific, and strongly influenced by societal changes, goals, standards, and objectives [21][22][23]. Further, pedagogical competence is influenced by teacher education, which, in turn, affects the context in which the teachers operate [23,24].…”
Section: Teachers' Pedagogical Expertise In Ecementioning
confidence: 99%
“…From a wider perspective, pedagogical competence is combined with an examination of learning experiences from a child's perspective. The teacher understands the learners, considers their personalities and feelings, and identifies what kind of skills or opportunities the students have to learn [21]. Teachers evaluate their relationships with students, and students' relationships with each other, and help students reach their potential.…”
Section: Teachers' Pedagogical Expertise In Ecementioning
confidence: 99%
See 2 more Smart Citations